Application of Bone Marrow–Derived Mesenchymal Stem Cells for Muscle Healing After Contusion Injury in Mice. Issue 5 (April 2020) - Chiu, Chih-Hao; Chang, Tsan-Hsuan; Chang, Shih-Sheng; Chang, Gwo-Jyh; Chen, Alvin Chao-Yu; Cheng, Chun-Ying; Chen, Su-Ching; Fu, Jen-Fen; Wen, Chih-Jen; Chan, Yi-Sheng
Background: Skeletal muscle injuries are very common in sports medicine. Conventional therapies have limited clinical efficacy. New treatment methods should be developed to allow athletes to return to play with better function. Purpose: To evaluate the in vitro differentiation potential of bone marrow–derived mesenchymal stem cells and the in vivo histologic and physiologic effects of mesenchymal stem cell therapy on muscle healing after contusion injury. Study Design: Controlled laboratory study. Methods: Bone marrow cells were flushed from both femurs of 5-week-old C57BL/6 mice to establish immortalized mesenchymal stem cell lines. A total of 36 mice aged 8 to 10 weeks were used to develop a muscle contusion model and were divided into 6 groups (6 mice/group) on the basis of the different dosages of IM2 cells to be injected (0, 1.25 × 10 5, and 2.5 × 10 5 cells with/without F-127 in 100 μL of phosphate-buffered saline). Histological analysis of muscle regeneration was performed, and the fast-twitch and tetanus strength of the muscle contractions was measured 28 days after muscle contusion injury, after injections of different doses of mesenchymal stem cells with or without the F-127 scaffold beginning 14 days after contusion injury. Results: The mesenchymal stem cell–treated muscles exhibited numerous regenerating myofibers. All the groups treated with mesenchymal stem cells (1.25 × 10 5 cells, 2.5 × 10 5 cells, 1.25 × 10 5 cells plus F-127, and 2.5 × 10 5 cells plus F-127) exhibited a significantly higher number of regenerating myofibers (mean ± SD: 111.6 ± 14.77, 133.4 ± 21.44, 221.89 ± 32.65, and 241.5 ± 25.95, respectively) as compared with the control group and the control with F-127 (69 ± 18.79 and 63.2 ± 18.98). The physiologic evaluation of fast-twitch and tetanus strength did not reveal differences between the age-matched uninjured group and the groups treated with various doses of mesenchymal stem cells 28 days after contusion. Significant differences were found between the control group and the groups treated with various doses of mesenchymal stem cells after muscle contusion. Conclusion: Mesenchymal stem cell therapy increased the number of regenerating myofibers and improved fast-twitch and tetanus muscle strength in a mouse model of muscle contusion. However, the rapid decay of transplanted mesenchymal stem cells suggests a paracrine effect of this action. Treatment with mesenchymal stem cells at various doses combined with the F-127 scaffold is a potential therapy for a muscle contusion. Clinical Relevance: Mesenchymal stem cell therapy has an effect on sports medicine because of its effects on myofiber regeneration and muscle strength after contusion injury.